2008
DOI: 10.3200/gntp.169.1.92-112
|View full text |Cite
|
Sign up to set email alerts
|

Social Problem Solving and Strategy Use in Young Children

Abstract: In the present study, the authors investigated what prosocial-assertive, passive, and coercive strategies 6-year-olds (N=257) would propose in response to stories about 2 socially challenging situations: displacing another child in a game and obtaining a toy from another child. The scenarios also varied the gender composition of the characters. Participants' verbalizations while acting out their responses using toy props fell into 13 categories of strategies. Teachers reported antisocial behavior and social co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 46 publications
1
29
0
2
Order By: Relevance
“…For example, overt aggression was associated with a hypervigilance to hostile cues (i.e., difficulty shifting their attention away from aggressive cues; [20]), attribution of hostile intent in ambiguous situations (''hostile attribution bias''; [21,22]), and aggressive response generation [23,24]. To assess SIP steps two through five, children were presented with hypothetical ambiguous peer provocation (e.g., being bumped) or problematic social situations (e.g., exclusion from an activity) via picture or video and then were asked to assess the intent of the target child and to state how they would response to the situation (e.g., aggressive, passive, competent).…”
Section: Social Information Processing As a Mediator Between Emotion mentioning
confidence: 99%
“…For example, overt aggression was associated with a hypervigilance to hostile cues (i.e., difficulty shifting their attention away from aggressive cues; [20]), attribution of hostile intent in ambiguous situations (''hostile attribution bias''; [21,22]), and aggressive response generation [23,24]. To assess SIP steps two through five, children were presented with hypothetical ambiguous peer provocation (e.g., being bumped) or problematic social situations (e.g., exclusion from an activity) via picture or video and then were asked to assess the intent of the target child and to state how they would response to the situation (e.g., aggressive, passive, competent).…”
Section: Social Information Processing As a Mediator Between Emotion mentioning
confidence: 99%
“…Many studies have shown that women/girls are more pro-social than men/boys (Abe- Kim, Okazaki, & Goto, 2001;Green et al, 2008;Malti, Gummerum, Keller, & Buchmann, 2009). Some studies, however, have found that boys use more pro-social strategies than girls (Rubin & Krasnor, 1983).…”
Section: Sharing: Individual Ownership Rights Versus Others' Well-beingmentioning
confidence: 91%
“…Children spontaneously use pro-social strategies (helping, offering objects) to maintain harmony among peers, but they also use coercive strategies (taking objects, insulting, being aggressive) to maintain their ownership rights when accessing a limited resource (Green, Cillessen, Rechis, Patterson, & Hughes, 2008). Such studies, which use classroom observation, have found that in kindergarten, children are actively concerned about ownership rights and others' well-being, but not much is known about how preschool children justify their actions when they have to choose between upholding personal rights and protecting others' well-being, especially in Chinese societies.…”
Section: Sharing: Individual Ownership Rights Versus Others' Well-beingmentioning
confidence: 99%
“…They found that in groups of girls, more collaborative strategies were used, while in groups of boys a greater number and range of strategies were used. In another study, Green et al (2008) explored the strategies used by six year olds when dealing with difficult social situations. They found that girls were more likely to suggest prosocial-assertive strategies with other girls than with boys, suggesting that girls are more socially competent with other girls than when interacting with boys.…”
Section: The Role Of Gender In Child Developmentmentioning
confidence: 99%
“…Green and Cillessen (2008) explored the behaviour of six year old children in play groups that demanded negotiation for preferred roles. They found that in groups of girls, more collaborative strategies were used, while in groups of boys a greater number and range of strategies were used.…”
Section: The Role Of Gender In Child Developmentmentioning
confidence: 99%